Kajian Sistem Drainase Perumahan di Kota Luwuk Kabupaten Banggai - P. Suartana (Civil Engineering Department, Tadulako University, 2023)
Luwuk City is the center of the city of Banggai Regency, which continues to grow. Urban development is followed by an increase in population and land requirements. Changes in land use from open land such as forests, gardens and dry fields to land for settlements causes surface water infiltration to decrease and increase surface runoff. Increased runoff due to reduced water catchment areas as the impact of city development has caused existing drainage to not be able to accommodate the increasing runoff water, resulting in waterlogging or even flooding. About 80% of the water used by the community is discharged directly as liquid waste into drainage canals. This condition of the community results in the accumulation of waste or silt in the drainage channels. This study aims to examine the drainage system in Luwuk City. The study was carried out by evaluating the existing canal system and identifying the suitability of the primary and secondary canals. Based on the results of the analysis carried out in this study, there are several things that can be concluded, namely: several drainage paths indicate the direction of flow does not follow the topography so that this can cause waterlogging and there are 3 natural channels that can be used as primary drainage and 6 natural channels that can be used as secondary drainage so that it will help speed up the flow of water to the final storage area